Antimicrobial resistance among Streptococcus pneumoniae and Haemophilus influenzae isolates in the United Arab Emirates: 2004-2006 - Abiola Senok,1 Mansour Al-Zarouni,2 Jal (The Journal of Infection in Developing Countries, 2007)
Background: Streptococcus pneumoniae and H. influenzae represent key aetiological agents in respiratory tract infections showing an increasing trend of antimicrobial resistance. We present the first report on the antimicrobial resistance in S. pneumoniae and H. influenzae isolated from patients in the United Arab Emirates.Methods: One hundred S. pneumoniae and 102 H. influenzae strains were isolated from patients with community acquired respiratory tract infections during the study period (October 2004-March 2006). Susceptibility testing to a panel of antibiotics was conducted using disc diffusion and E test. Minimum inhibitory concentrations were interpreted using CLSI and Pharmacokineticpharmacodynamic (PK/PD) breakpoints.Results: For S. pneumoniae isolates, 57% were penicillin susceptible while 98% were susceptible to amoxicillin/clavulanate with both interpretative criteria. Cefaclor was the least effective cephalosporin with only 57% and 43% of isolates showing susceptibility with CLSI and PK/PD breakpoints respectively. Thirty-six isolates were ofloxacin non-susceptible (intermediate and resistant); three resistant isolates were associated with high ciprofloxacin MICs (>8mg/L). There was elevated macrolide resistance with associated high levels of erythromycin/clindamycin cross-resistance (n=22/30) suggesting predominant erm(B)-mediated resistance and 21% of isolates demonstrated multidrug resistance. For H. influenzae, 18% were beta-lactamase producers. Reduction in cefaclor and cefprozil susceptibility with PK/PD breakpoints (94.1% to 41.2% and 62.7% respectively) was seen and only 1% remained azithromycin and clarithomycin susceptible. For both pathogens, lowest susceptibility was with co-trimoxazole.Conclusion: These findings indicate a high level of penicillin resistance and continued usefulness of amoxicillin/clavulanate. Elevated macrolide and fluoroquinolone resistance and the occurrence of multidrug resistance indicate a need for continued surveillance.